2021
DOI: 10.1021/acssuschemeng.1c01737
|View full text |Cite
|
Sign up to set email alerts
|

New Approach to Recycling of Epoxy Resins Using Nitric Acid: Regeneration of Decomposed Products through Hydrogenation

Abstract: Due to the increase in the amount of produced epoxy resin waste, it is desirable to recycle this material to reduce the burden on the environment. Despite many studies focusing on recovering fibers from composites, few studies have focused on recycling the resin itself. In this study, we developed a new approach for recycling the decomposed amine-cured epoxy resin as an amine curing agent. Following the decomposition of the epoxy resin in nitric acid, a nitrated and decomposed resin product was extracted from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…The hydrogenated extract can replace 20 wt% of the conventional amine curing agent in amine-cured epoxy resins. 55 Ma et al used glacial acetic acid/H 2 O 2 solution to degrade amine-cured epoxy resins, and employed the recovered products as the catalyst and filler for anhydride-cured epoxy resins. 56 Xu et al reported that microwave-assisted catalysis was capable of degrading dichloromethane treated anhydride-cured epoxy resins at 130 °C.…”
Section: Introductionmentioning
confidence: 99%
“…The hydrogenated extract can replace 20 wt% of the conventional amine curing agent in amine-cured epoxy resins. 55 Ma et al used glacial acetic acid/H 2 O 2 solution to degrade amine-cured epoxy resins, and employed the recovered products as the catalyst and filler for anhydride-cured epoxy resins. 56 Xu et al reported that microwave-assisted catalysis was capable of degrading dichloromethane treated anhydride-cured epoxy resins at 130 °C.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the same group treated the DP obtained from the depolymerization of an aliphatic amine cured BPA epoxy in nitric acid by hydrogenation which converted the –NO 2 group of DP to amine groups. [ 88 ] The treated DP was used as a curing agent and replaced 10 wt.% of the original amine curing agent, and the resulting product exhibited comparable tensile properties to that of the virgin resin. Although this method is interesting, the hydrogenation treatment would significantly add cost to the recycling process, limiting its practical application.…”
Section: Reuse Of Degraded Polymer Matrixmentioning
confidence: 99%
“…12,13 In comparison, oxidative degradation has significant advantages in energy efficiency which can be performed at atmospheric pressure with a temperature lower than 90 °C. [14][15][16][17][18][19][20][21][22][23][24][25] Use of common oxidants or catalysts has been reported for the degradation of EP including hydrogen peroxide, 14,16,25 nitric acids, 18,21,22,24 ruthenium trichloride, 15 sodium hypochlorite, 19 potassium permanganate, 20 and so on. Among these, hydrogen peroxide is preferred because of its high redox potential and clean process with water as the only by-product.…”
Section: Introductionmentioning
confidence: 99%